2022
DOI: 10.1101/2022.04.30.22274189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Then and NOW: A Prospective Population-Level Validation of the Abbott ID NOW SARS-CoV-2 Device Implemented in Multiple Settings for Testing Asymptomatic and Symptomatic Individuals

Abstract: INTRODUCTION Since December, 2020, the ID NOW was implemented for use in 4 different populations across Alberta: in mobile units as part of community outbreak response, COVID19 community collection sites, emergency shelters and addiction treatment facilities (ES), and hospitals. OBJECTIVE Diagnostic evaluation of the ID NOW in various real world settings among symptomatic and asymptomatic individuals METHODS Depending on the implemented site, the ID NOW was tested on patients with symptoms suggestive of COVID-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…However, we previously observed no differences in sensitivity based on common patient, collecting and testing characteristics, including age, gender, and swab type. 2 Our current study also did not demonstrate any difference in performance with these characteristics, though the sample size was not large enough to make any concrete conclusions. Another limitation is the inability to exclusively study Omicron by itself.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…However, we previously observed no differences in sensitivity based on common patient, collecting and testing characteristics, including age, gender, and swab type. 2 Our current study also did not demonstrate any difference in performance with these characteristics, though the sample size was not large enough to make any concrete conclusions. Another limitation is the inability to exclusively study Omicron by itself.…”
Section: Discussioncontrasting
confidence: 60%
“…In the face of Omicron, our study demonstrated increased ID NOW sensitivity compared to prior variant waves. 2 The ID NOW sensitivity in assessment centres before Omicron (as of November 24, 2021) was 92.5% (95% CI 92.0-93.0%). Our current data during the Omicron wave has demonstrated a higher ID NOW sensitivity of 96.0% (95% CI 94.5-97.3%).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations